(untitled) (Dissertare, 2019)
The research portrays the 21st century manager’s profile, from the focus of the intelligent organization (Senge, 2005), adopting as a population the microenterprises of the telecommunications sector of the Iribarren municipality, Lara state (Venezuela). An intentional sample of 5 organizations was chosen and the survey and interview techniques were used, through the application of a questionnaire and unstructured interviews. The study presents a mainly quantitative, descriptive approach with field design and contemplates some aspects of qualitative approach that serve as the basis for the formulation of a theoretical model of the 21st century manager (21stCM)’s profile. The 21stCM model proposes 10 characteristics of the manager that recognize shared meanings and encourage their adaptation aimed at achieving objectives regardless of technological changes or new management models. The results show that the managers of the analyzed microenterprises generally perform the traditional managerial functions, but show an inclination towards the disciplines of the intelligent organization, with emphasis on shared vision and team learning. Managers consider planning important, but do not use it as a learning tool, within the discipline of mental models. It is concluded that managers are biased towards the planning and control functions, applied together with elements of the intelligent organization approach, however, weaknesses in the discipline of mental models are appreciated, so it is recommended to reinforce strategies aimed at investigate and overcome these ways of thinking.